2021
DOI: 10.1101/2021.10.19.21265189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for Influenza and RSV interaction from 10 years of enhanced surveillance in Nha Trang, Vietnam, a modelling study

Abstract: Influenza and Respiratory Syncytial Virus (RSV) interact within their host posing the concern for heterologous ecological changes following vaccination. We aimed to estimate the population level impact of their interaction. We developed a dynamic age-stratified two-pathogen mathematical model that includes pathogen interaction through competition for infection and enhanced severity of dual infections. We used parallel tempering to fit it's parameters to 11 years of enhanced hospital-based surveillance for ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 46 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…While estimates for RSV are less certain, past modeling work has suggested that immunity persists for at least one year 37, 69 . Furthermore, our assumption is consistent with other RSV modeling work, which also does not account for within-season waning of immunity 23, 70 . Average infectious periods were fixed at 5 days for influenza 71 and 10 days for RSV 72, 73 .…”
Section: Methodssupporting
confidence: 88%
See 4 more Smart Citations
“…While estimates for RSV are less certain, past modeling work has suggested that immunity persists for at least one year 37, 69 . Furthermore, our assumption is consistent with other RSV modeling work, which also does not account for within-season waning of immunity 23, 70 . Average infectious periods were fixed at 5 days for influenza 71 and 10 days for RSV 72, 73 .…”
Section: Methodssupporting
confidence: 88%
“…Past research has yielded mixed results concerning the severity of coinfections with influenza and RSV: some studies have found coinfections to be more severe than infections with either virus alone 60, 61 , while others have found evidence of reduced severity 12, 15 . In the modeling study of influenza and RSV cocirculation in Vietnam discussed above, the fitted model was most consistent with a 2-20 times increase in reporting among coinfected individuals 23 . We attempted to fit our model allowing for a change in infection severity among coinfected individuals but found that this effect was not identifiable.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations